Wireless Pressure Sensing Smart Stent for Enhanced Post-Endovascular Aneurysm Repair (EVAR) Surveillance - Jun Ying Tan; Cheolbok Kim; Trisha Das Mou; Albert Kim; Jungkwun 'Jk' Kim (IEEE Access)
Continuous post-endovascular aneurysm repair (EVAR) surveillance is critical for patients who have undergone a stenting procedure. Despite its life-saving importance, studies have reported that patients gradually discontinue post-EVAR surveillance due to the significant burden associated with CT scans, X-rays, etc. Considering the importance and necessity of post-EVAR surveillance, we introduce a self-resonating flexible tube implanted in a standard clinically approved stent that enables wireless sensing of blood pressure inside an aneurysm through inductive coupling. To enable blood pressure monitoring outside the body, we designed and fabricated a spiral-type antenna, specifically crafted to capture the inherent resonance frequency of the self-resonating stent tube. To showcase the wireless pressure monitoring capability, a 3D-printed elastic model of an abdominal aortic aneurysm (AAA) was prepared. Our quantitative study validated the pressure-sensing capability with adequate sensitivity (up to 687.5 Hz/mmHg) when tissue was located between the stent and the external antenna. The wireless sensing also presents a consistent linear shift in resonance frequency across all tested measuring distances as the applied pressure ranges from 60 to 140 mmHg. The proposed self-resonating stent offers promising insights for improving post-EVAR surveillance.